Strategi Komunikasi Sebaya Duta GenRe: Integrasi Homofili dan Nilai Budaya Sunda dalam Pencegahan Stunting - Dwi Rini Sovia Firdaus (Universitas Pakuan, 2026)
This study analyzes the communication strategies of Generation Planning Ambassadors (Duta GenRe) in the Zero Growth Stunting program in Bogor City by integrating social psychology perspectives and Sundanese cultural values. Employing a qualitative descriptive approach with in-depth interviews with key informants from DPPKB, GenRe Forum, GenRe Ambassadors, and community members, the study finds strategies encompassing: (1) selection of credible peer communicators based on psychological homophily; (2) target segmentation by psychological vulnerability; (3) message construction integrating Sundanese values of silih asah, silih asih, silih asuh; and (4) media selection adapted to urban Sundanese youth's cognitive preferences. The study proposes a three-layer peer communication model (psychological–cultural–structural) as its theoretical novelty, contributing to the development of culturally sensitive and socially psychology-based health communication models.